(untitled) (International Journal of Agriculture and Sustainable Development, 2021)
The delicate balance between ecology and biodiversity is maintained by Nature. Any disruption to this equilibrium might have devastating impacts on the environment, including plants, animals, and people. As a result, conservation efforts are necessary to keep the diversity of life on earth healthy. New issues for agriculture have evolved as a result of the current era of global warming and climate change. One of the most serious issues facing Pakistani farmers is preserving the country’s natural resources and biodiversity. It is imperative to take preventive measures now to prevent further biodiversity losses. Study participants were asked about their level of awareness of biodiversity conservation. Generally, farmers were aware of species diversity, but many were not aware of modern methods for preserving crop and species diversity. Farmers have limited awareness of biodiversity and only a few tried-and-true ways for preserving it. Two-way statistical analysis found a weakly significant link between variables responsible for biodiversity loss and two categories of biodiversity, concluding that not all causes are equally responsible for biodiversity loss in both types. According to the findings, agricultural development relies heavily on biodiversity conservation. Conserving biodiversity can increase agricultural output. Using Exploratory Factor Analysis, it was discovered that retaining three factors increased the explained variation to 54%.